2014
DOI: 10.1101/cshperspect.a015172
|View full text |Cite
|
Sign up to set email alerts
|

The Genetics of Human Skin Disease

Abstract: The skin is composed of a variety of cell types expressing specific molecules and possessing different properties that facilitate the complex interactions and intercellular communication essential for maintaining the structural integrity of the skin. Importantly, a single mutation in one of these molecules can disrupt the entire organization and function of these essential networks, leading to cell separation, blistering, and other striking phenotypes observed in inherited skin diseases. Over the past several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 174 publications
0
20
0
Order By: Relevance
“…As predicted, we found a significant enrichment within the HLA locus of chromosome 6 (6p21.3), with 18.5% (37/200) of inflammatory HiChIP-SNPs localizing to this region Abbreviations: ChIP, chromatin immunoprecipitation; SLE, systemic lupus erythematosus; SNP, single nucleotide polymorphism. (Figure 2a) (DeStefano and Christiano, 2014;Matzaraki et al, 2017). Approximately one third of SNP-TSS interactions (471/1,404) from inflammatory conditions reside at the HLA locus, many of which target genes directly involved in antigen processing and presentation ( Figure 2b and Supplementary Figure S1a).…”
Section: Inflammatory Snps Are Enriched Within Hla Locusmentioning
confidence: 99%
See 1 more Smart Citation
“…As predicted, we found a significant enrichment within the HLA locus of chromosome 6 (6p21.3), with 18.5% (37/200) of inflammatory HiChIP-SNPs localizing to this region Abbreviations: ChIP, chromatin immunoprecipitation; SLE, systemic lupus erythematosus; SNP, single nucleotide polymorphism. (Figure 2a) (DeStefano and Christiano, 2014;Matzaraki et al, 2017). Approximately one third of SNP-TSS interactions (471/1,404) from inflammatory conditions reside at the HLA locus, many of which target genes directly involved in antigen processing and presentation ( Figure 2b and Supplementary Figure S1a).…”
Section: Inflammatory Snps Are Enriched Within Hla Locusmentioning
confidence: 99%
“…Over the past decades, genome-wide association studies (GWASs) have identified a large number of single nucleotide polymorphisms (SNPs) associated with complex dermatologic diseases (DeStefano and Christiano, 2014). However, up to 90% of GWAS-identified SNPs fall in noncoding DNA regions (Altshuler et al, 2008;Edwards et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Psoriasis is a complex genetic disease with at least 41 genetic susceptibility loci contributing to the pathogenesis [76], and there continues to be progress towards deciphering the genetics of other skin diseases as well [77]. Considering the additional influence of environmental factors [78], it is tempting to argue that studies focused exclusively on genetically homogenous inbred mice, despite all their advantages, can never succeed in fully replicating human diseases and their complexity [79].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, forward genetics is a phenotype-togene approach that begins with a mutant phenotype of interest and proceeds to the identification of the disrupted gene. Both methods have been used to elucidate genes required for protection against dermatologic disease (DeStefano and Christiano, 2014). Reverse genetics generally involves prior knowledge or speculation as to how a gene may function, which can limit the finding of novel and unexpected pathways leading to a disease phenotype.…”
Section: Introductionmentioning
confidence: 99%